Educational challenges of postgraduate neonatal intensive care nursing students: A qualitative study - Monirsadat Nematollahi; Fatemeh Esmaelzadeh; Roghayeh Mehdipour-Rabori; Behnaz Bagherian (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Despite the progress of health care and the application of new technology in the care of patients, the need to train highly skilled and specialized nurses is inevitable. Given that a master's degree in neonatal intensive care nursing has been recently established in Iran, the aim of the study was to explain the educational challenges of neonatal intensive care postgraduate nursing students in their perspective. MATERIALS AND METHODS: This conventional content analysis was performed by conducting semi-structured interviews with 18 students of neonatal intensive care in X University of Medical Sciences from 2018 to 2019. Data were analyzed using conventional content analysis. To establish the reliability and validity of findings, Graneheim and Landman criteria were considered. RESULTS: Following the data analysis, two main categories were extracted: "theoretical education challenges" and "clinical education challenges." The first main category was comprised of the following subcategories: "detachment of nursing department and hospital," "defects in weekly scheduling," "combination of care and treatment approaches in education," "inconsistency between the content of theoretical courses," "limited collaboration between basic science and medical departments," "low number of lecturers," "lecturers' unrealistic expectations," and "the importance of the scoring system." "Extended work shifts," "a large number of students," "lack of opportunity to do clinical practices," "lack of training classes," and "limited amenities in the hospital" were recognized as subcategories of the second category. CONCLUSION: Managers can address some of the students' challenges and provide the opportunity to enhance the quality of education through being familiar with, considering and meetings the needs and expectations of these students.